RF-driving of acoustic-optical tunable filters; design, realization and qualification of analog and digital modules for ESA. Issue 9 (August 2015) - Vanhamel, J.; Fussen, D.; Dekemper, E.; Neefs, E.; Van Opstal, B.; Pieroux, D.; Maes, J.; Van Lil, E.; Leroux, P.
Abstract: The ALTIUS-instrument is a three-channel spectral imager, measuring in the ultraviolet, visible and near infrared wavelength domains, that is bound to fly aboard a PROBA-satellite. The goal of the ALTIUS-instrument is to make hyper spectral images of the limb of the earth. In each of ALTIUS' three channels an AOTF (Acousto-Optical Tunable Filter) will be used. For each channel an RF-generator will be developed and subjected to a suite of environmental tests such as thermal-vacuum, vibration, radiation, shock and Electromagnetic Compatibility (EMC). For the AOTF RF-generator different solutions are possible. Currently the design of an analog Hilbert transform and a high frequency phase-locked loop (PLL) are proposed as possible solutions. The choice of components, the PCB-design and the manufacturing of both designs has to be done in accordance to space qualified standards. This limits the choice of design and lifts the design challenge to a higher level. Because of the limited choice of space qualified components, general commercial approaches are not possible. For this reason specific designs have to be investigated and research has to be done to select the appropriate solution. Highlights: Two different approaches have been presented for the design of an RF-generator. Solutions are selected based on the availability of space qualified components. The Hilbert transform and a PLL-based approach are tested, measured and compared. A preliminary design of an RF-amplifier for space applications is investigated. Impedance behavior of the AOTFs is measured and results are shown.